2019
DOI: 10.1155/2019/2182471
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Protein A on Monodisperse Magnetic Nanoparticles for Biomedical Applications

Abstract: We presented synthesis and physical characterization of iron oxide magnetic nanoparticles (Fe3O4) for biomedical applications in the size range of 10-30 nm. Magnetic nanoparticles were synthesized by the coprecipitation method, and the particles’ size was controlled by two different injection methods of sodium hydroxide (NaOH). The synthesized magnetic nanoparticles were then modified by using series of linkers including tetraethyl orthosilicate (TEOS), 3-aminopropyltriethoxysilane (APTES), and glutaraldehyde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…In order to couple enzymes to solid supports, we chose Sortase A (SrtA) to enable both oriented immobilization and physiological coupling conditions, thus retaining functionality of coupled enzymes. In recent years, magnetic nanoparticles (MNPs) emerged as a new standard for protein immobilization mainly because of their versatility and easy handling. , Therefore, we decided to combine the advantages of SrtA-mediated protein immobilization and MNPs. In order to equip MNPs with a polypeptide which serves as a SrtA substrate, we chose a peptide (peptide 1) based on repeating sequences of commonly used polyGly/Ser motifs providing flexibility and solubility .…”
Section: Results and Discussionmentioning
confidence: 99%
“…In order to couple enzymes to solid supports, we chose Sortase A (SrtA) to enable both oriented immobilization and physiological coupling conditions, thus retaining functionality of coupled enzymes. In recent years, magnetic nanoparticles (MNPs) emerged as a new standard for protein immobilization mainly because of their versatility and easy handling. , Therefore, we decided to combine the advantages of SrtA-mediated protein immobilization and MNPs. In order to equip MNPs with a polypeptide which serves as a SrtA substrate, we chose a peptide (peptide 1) based on repeating sequences of commonly used polyGly/Ser motifs providing flexibility and solubility .…”
Section: Results and Discussionmentioning
confidence: 99%
“… A previous study could show the competitiveness of Protein G immobilized on such nanoparticles in direct comparison with chromatographic beads . Several studies focus on the use of magnetic nanoparticles as carrier material for Protein A and suggest their applicationfor antibody purification and sensorics. Typically, these particles are modified with functional silanes or saccharide-based polymers to subsequently cross-link Protein A to the activated particles. Even if thin and homogeneous coatings are possible, the processing of the particles increases their size compared to bare iron oxide nanoparticles (BION) and decreases their magnetization .…”
Section: Introductionmentioning
confidence: 99%
“…The main pathways involved in the interactions of proteins with MNP surfaces are electrostatic attraction/repulsion, hydrophobic attraction/repulsion, Van der Waals interactions, and coordinative bonding [ 84 ], and it has been shown that proteins bind with MNPs via carboxyl groups [ 85 ]. Despite the fact that the overall mechanism and driving forces of such interactions remain unclear [ 86 ], this has not hindered scientists from using proteins for MNP functionalization for the creation of new facilities for biomedical applications [ 87 , 88 , 89 ].…”
Section: Mnp Synthesis Surface Coating and Functionalizationmentioning
confidence: 99%